Social gaze dynamics in teams: Comparing face-to-face and video meeting settings - Petra Nieken; Tom F. Reuscher (PLoS ONE, 2026)
Understanding the factors that promote cooperative behavior in teams is essential for organizational success. While the role of verbal communication in fostering cooperation and team cohesion is well established, the impact of nonverbal signals, particularly eye contact and related patterns, known as social gaze dynamics, has been neglected. In this study, we conducted a multiparty eye-tracking experiment, enabling us to explore the relationship between social gaze, cooperation, and team cohesion. In particular, teams of three participants engaged in a two-stage task: a structured pre-play communication stage (1) and a social dilemma game (2). During pre-play communication, eye-tracked participants performed a real-effort task mirroring the ensuing social dilemma. This allowed us to capture social gaze dynamics and assess their relation to subsequent cooperation and team cohesion. Specifically, we compared the emergence and impact of attentional reciprocity between face-to-face and video meeting settings and provided initial evidence that the extent to which direct gaze is reciprocated within teams influences subsequent cooperative behavior. Overall, our findings highlight potential downsides of increasingly shifting team meetings to the virtual space, where the absence of gaze information affects the emergence and impact of social gaze dynamics.